2015
DOI: 10.1088/0031-9155/60/9/3807
|View full text |Cite
|
Sign up to set email alerts
|

3D fluoroscopic image estimation using patient-specific 4DCBCT-based motion models

Abstract: 3D fluoroscopic images represent volumetric patient anatomy during treatment with high spatial and temporal resolution. 3D fluoroscopic images estimated using motion models built using 4DCT images, taken days or weeks prior to treatment, do not reliably represent patient anatomy during treatment. In this study we develop and perform initial evaluation of techniques to develop patient-specific motion models from 4D cone-beam CT (4DCBCT) images, taken immediately before treatment, and use these models to estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 48 publications
5
37
0
Order By: Relevance
“…7,8 Of these, recent interest has focused on the DTT technique, which is able to dynamically reposition the radiation beam or the robotic couch in accordance with the position of the target. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] DTT decreases internal uncertainties due to target motion, without the need for a prolonged treatment time or the burden of shallow breathing or breath-holding for patients. There are two approaches to achieving DTT: direct and indirect tracking methods.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Of these, recent interest has focused on the DTT technique, which is able to dynamically reposition the radiation beam or the robotic couch in accordance with the position of the target. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] DTT decreases internal uncertainties due to target motion, without the need for a prolonged treatment time or the burden of shallow breathing or breath-holding for patients. There are two approaches to achieving DTT: direct and indirect tracking methods.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the time synchronized CBCT (4DCBCT) method has been introduced to manage respiration-induced target motion during treatment verification imaging. [22][23][24][25][26][27][28][29][30] In 4DCBCT imaging, two-dimensional (2D) projections acquired at different times and positions are sorted into several groups, according to their respiratory phases, and each phase group is then reconstructed independently to obtain a volumetric image corresponding to that specific phase. The respiratory wave required for retrospective 4DCBCT reconstructions is derived using either 2D projections of CBCT itself or an external surrogate system.…”
mentioning
confidence: 99%
“…High correlations (0.94–0.98 and 0.98 ± 0.02) have been reported between the diaphragm and tumor motion in lung (Cervino et al 2009) and liver patients (Yang et al 2014). Reports have shown that diaphragm motion can be used as a surrogate for tumor motion without implanted fiducials (Li et al 2009c, Lin et al 2009, Dhou et al 2015). In cine megavoltage electronic portal imaging during beam-on time, initial study has shown the feasibility of extracting volumetric treatment images based on 4DCT-based motion modeling (Mishra et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In cone-beam CT (CBCT) imaging, projection images can be utilized by combining deformable image registration and principal component analysis (PCA) to estimate the tumor position with the diaphragm as the major anatomic landmark (Zhang et al 2007, Li et al 2010a, 2010b, Li et al 2011). In other CBCT studies, an automatic method was developed to detect the diaphragm motion (Siochi 2009, Chen and Siochi 2010, Dhou et al 2015). In 4DCT reconstruction, the diaphragm can be used as an internal surrogate for respiratory binning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation